Median Road Revitalization as an Alternative Way to Overcome Flood on Jalan Asrama, Helvetia, Medan - Indonesia - Suryo Sukarno P. K; Luthfi Audi; Muhammad Danesh (International Journal of Architecture and Urbanism, 2020)
Jalan Asrama, Helvetia Medan, is one of the areas in Medan that is often flooded. The puddle of water on Jalan Asrama, especially at the intersection of Gaperta Street, is already very alarming because the puddles that occur can reach heights of up to 0.5 meters so that it greatly disrupts traffic activity at that location. The cause is the inadequate condition of infrastructure facilities; one of the infrastructures referred to is the drainage and utilization of the Median Road that is not optimal. The purpose of this research is to find out the factors that cause flood inundation on the road bodies around Jalan Asrama-Medan following offer a solution by revitalizing the median Road as one way to overcome the flood. The research method used descriptive qualitative research methods. Namely by conducting research directly into the field and conducting library studies on various types of reading material related to the object of study in this study, among others in the form of books, journals, articles, and written works in the form of print media and internet media. This study concludes that the occurrence of inundation in the bodies of roads around Jalan Asrama, Helvetia, is caused by several factors. First, high rainfall, the two dimensions of drainage channels are not suitable in some parts; third is sedimentation and rubbish, which reduce the dimensions of the channel and inhibit the flow rate of water. Moreover, one solution that can be done is to revitalize the median of the road, which hopes can overcome the flood.